Application Of Differentiated Learning In The Independent Curriculum In Elementary School - Ain, Lulu Huril (UIN Siber Syekh Nurjati Cirebon, 2024)
The implementation of differentiated learning in the Independent Curriculum in elementary schools highlights efforts to meet the diverse learning needs of students. The Merdeka Curriculum prioritizes flexibility in teaching with the aim of empowering schools to adapt learning strategies to the individual characteristics of each student. This article reviews the basic concepts of differentiated learning, highlighting the importance of adapting the curriculum to accommodate students' learning styles, comprehension speeds, and interests. The method used in the research is the SLR (Systematic Literature Review) method by processing articles that are in accordance with the discussion. According to the results of systematic reviews of various published studies, it is possible that materials, processes, products, and learning environments can change with differentiated learning. This learning can boost students' enthusiasm to develop their own potential and during learning activities. Through literature analysis, this approach has been shown to increase students' active participation, learning motivation, and overall academic achievement. However, implementation challenges and training needs for educators are also discussed to ensure the effectiveness of differentiated learning in the context of the Independent Curriculum in Primary Schools. Further research is recommended to measure the long-term impact of this approach on student development and educational equity in Indonesia.Keywords:differentiated learning, independent curriculum, application, elementary.